O homo ludens no contexto da dialética platônica na alegoria da caverna: os jogos como estratégia lúdica para o ensino de Filosofia - CARVALHO, Eveline Maria da Conceição Sousa e Silva de (2020)
This dissertation is the result of a research carried out at the Federal Institute of a Science and Technology Education - IFMA Campus Monte Castelo class 213 of the 1 st Year of the building course, for the Professuinal Master in Philosophy, with the objective a playful strategy-the game for the Philosophy teaching, which can be extended to other areas of knowledge. The main theoretical references are guided from the historian Johan Huizinga, who assumes that the individual, in addition to thinking and manufacturing, is also playful; in addition to the work The Republic of the philosopher Plato and form where the platonic Dialectic is as a Game in which the wold-be philosopher needs to pass, intellectually destroying the hipotheses to reach the knowledge of Ideal Forms - The intelligible woed. Thus, it is at the junction of the ideal of Homo Ludens de Huizinga with the Platonic Dialectic, that the research carried out in class 213 has been made in this dissertation. Emphasizing that there is no pedagogical arrogance that the teaching strategy woul be the most effective, but rather a contributing strategy for ways to better manage knowledge. The dissertation took place with the Laboratory Method, with a mixed approach: qualitative and quantitative.